The Effect of Net Profit Margin, Debt to Equity Ratio, and Return on Equity against Company Value in Food and Beverage Manufacturing Sub-sector Companies listed on the Indonesia Stock Exchange - Janice Janice; Nagian Toni (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
This research deals with the effect of net profit margin, debt to equity ratio, and return on equity against company value in food and beverage manufacturing sub-sector companies listed on the Indonesia stock exchange. The variables in this study are described using descriptive statistics. The result shows that Partially, Net Profit Margin has no effect on the company value in food and beverage companies on the Indonesia Stock Exchange in 2014-2018. Partially, Debt to Equity has no effect on the company value in food and beverage companies on the Indonesia Stock Exchange in 2014-2018. Partially, Return on Equity affects the company value in food and beverage companies on the Indonesia Stock Exchange in 2014-2018.